The Gospel of John as literature : an anthology of twentieth-century perspectives - Stibbe, Mark W. G. (New Testament tools and studies, 1993)
This volume contains thirteen essays written between 1900 and today. Each of them takes as its starting point the Gospel of John as a literary unity. The volume as a whole traces literary studies of John back to the early 1900's and charts their development from then. Some of these essays are little known even to Johannine scholars. Others are recognized as classics in the field. Two of them are translations. This book is therefore a timely and indispensable resource for those interested in the history of the fourth gospel interpretation, and in examples of literary methods applied to John.